Determination of Tramadol Hydrochloride by Using UV and Derivative Spectrophotometric Methods in Human Plasma - Kucuk, Aysel; Kadioglu, Yucel (Asian Journal of Chemistry, 2010)
Tramadol was analyzed by using zero-, first- and second-order derivative spectrophotometric methods in methanol and water media. The type of solvent, the degree of derivation, the range of wavelength and the range of concentration were chosen in order to optimise the conditions. The developed and validated method was successfully applied to the analysis of human plasma samples in methanol medium. Beer's law was obeyed in the linearity range of 10-100 μg mL-1 between the wavelength ranges of 240-290 nm. The solutions of standard were prepared in methanol and water media and the plasma samples were prepared in methanol medium. It was thought that methanol is more suitable solvent than water for tramadol analysis in human plasma. The standard calibration curves of tramadol were constructed by plotting absorbance versus concentration in the determined concentration range with the final dilution. Developed UV and derivative UV spectrophotometric methods in this study are accurate, sensitive, precise and reproducible and can be directly and easily applied to the plasma.